First‐in‐man controlled rewarming and normothermic perfusion with cell‐free solution of a kidney prior to transplantation. Issue 4 (10th November 2019) - Minor, Thomas; von Horn, Charlotte; Gallinat, Anja; Kaths, Moritz; Kribben, Andreas; Treckmann, Jürgen; Paul, Andreas
Abstract : Cold preservation sensitizes organ grafts to exacerbation of tissue injury upon reperfusion. This reperfusion injury is not fully explained by the mere re‐introduction of oxygen but rather is pertinent to the immediate rise in metabolic turnover associated with the abrupt restoration of normothermia. Here we report the first clinical case of gradual resumption of graft temperature upon ex vivo machine perfusion from hypothermia up to normothermic conditions using cell‐free buffer as a perfusate. A kidney graft from an extended criteria donor was put on the machine after 12.5 hours of cold storage. During ex vivo perfusion, perfusion pressure and temperature were gradually elevated from 30 mm Hg and 8°C to 75 mm Hg and 35°C, respectively. Perfusate consisted of diluted Steen solution, oxygenated with 100% oxygen. Final flow rates at 35°C were 850 mL/min. The kidney was transplanted without complications and showed good immediate function. Serum creatinine fell from preoperative 720 µmol/L to 506 µmol/L during the first 24 hours after transplantation. Clearance after 1 week was 43.1 mL/min. Controlled oxygenated rewarming prior to transplantation can be performed up to normothermia without blood components or artificial oxygen carriers and may represent a promising tool to mitigate cold‐induced reperfusion injury or to evaluate graft performance. Abstract : This report demonstrates clinical feasibility of an acellular ex vivo organ perfusion, including controlled oxygenated rewarming from the cold up to normothermia, prior to successful transplantation of an extended criteria donor kidney.